Interaction between continental and estuarine waters in the wetlands of the northern coastal plain of Samborombón Bay, Argentina - Carol, Eleonora Silvina (2013)
On the Samborombón Bay coastline, located in the Río de la Plata estuary in Buenos Aires province (Argentina), a complex hydrological system has developed at the interface between continental and estuarine water, where significant wetlands develop. The main hydrogeological units, namely the shell ridges, the tidal plain and the marsh areas, have been identified using geomorphological criteria. Water table, hydrochemical and isotopic data have been used to determine their hydrological features, as well as those of the streams and canals. Evaporation processes, in particular, have been considered when depicting chemical and isotopic changes in surface waters in streams and marsh areas. The shell ridges represent a hydrogeological unit in which rainwater is stored, constituting a lens-shaped freshwater aquifer. In this unit, just as in the tidal plain, carbonate dissolution and ion exchange are the main processes regulating water chemistry. On the other hand, in the marsh and surface waters, processes such as mixing with estuarine water and evaporation predominate. These processes control water fluxes and the salinity of the wetland areas and, consequently, their ability to preserve the existing biodiversity. This study shows the importance of knowledge of hydrochemical processes in any proposal concerning the management and preservation of this type of wetland.